GE_GERICHTE P/26522/2017 vom 23. April 2019 - GE Cour de justice (2019)
COMPÉTENCE RATIONE MATERIAE ; AUTORITÉ DOUANIÈRE ; TRIBUNAL PÉNAL ; CONVERSION DE LA PEINE | CPP.363.al3; LaCP.50; LaCP.41; LaCP.42; DPA.10.letc